Measuring time attitudes in Slovenia - Juriševič, Mojca (Psihološka obzorja (Ljubljana), 2017)
In the present study, we examined the psychometric properties of scores on the newly developed Slovenian version of the Adolescent and Adult Time Inventory-Time Attitudes Scale (AATI-TA) in a sample of 182 Slovenian adolescents. The 30-item AATI-TA assesses positive and negative attitudes towards the past, present, and the future. Time attitudes are particularly important in adolescence due to their association with various educational and psychological outcomes. The AATI-TA is a robust instrument and AATI-TA scores have already been validated in several national contexts worldwide. Due to language differences between Slovene and English, a 24-item version of the AATI-TA was examined in Slovenia. As hypothesized, scores on the 24-item Slovenian version of AATI-TA were internally consistent and structurally valid. Moreover, meaningful correlations between time attitudes and positivity, a basic disposition determining individual well-being, provided evidence of concurrent validity. The results suggest that the Slovenian version of the AATI-TA will be useful in Slovenian research examining time attitudes.
Keywords: mladostništvo; odraslost; merjenje stališč; čas; zaznavanje časa; čustva; blagostanje; Inventar o času za mladostnike in odrasle - Lestvica stališč do časa AATI-TA (slovenska različica)